Orientarsi tra due mondi: i percorsi linguistici di Unige tra scuola e università - Rita Cersosimo; Nora Gattiglia; Alice Pagano; Micaela Rossi; Giulia Staggini (MediAzioni)
This paper illustrates the activities proposed by the Department of Modern Languages and Cultures (DLCM) of the University of Genoa, carried out within the framework of the POT (Plans for Orientation and Tutoring) and PCTO (Pathways for Transversal Competences and Orientation) projects promoted by MIUR, starting from 2017 and addressed to students of secondary schools. The described workshop experiences focus on two macro-areas in particular: on the one hand, an experiential pathway on the profession of interpreter; on the other, the enhancement of language skills. In conclusion, future objectives are described in the perspective of a more inclusive university.